DEALING WITH STUDENT BEHAVIOUR PROBLEMS IN THE CLASSROOM (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Student behavior problems pose significant challenges at all educational levels. This article aimed to identify the types, prevalence, and intricate nature of these issues, as well as their impact on teaching and learning. Researchers analyzed archival data on discipline referrals from a middle school. The findings revealed that "Insubordination" was the most common reason for referrals, followed by "Disruption of school/class activity" for both regular and special education students. Referrals for "Use of violence" and "Vulgar language" were less common for both groups. Boys received more referrals than girls, with 74% of regular education and 91% of special education referrals involving male students. The highest rate of behavior problems occurred during the lunch period. The article also explores parental and school factors contributing to these behavior issues and discusses successful intervention and prevention strategies used in similar situations.